Kif1bp loss in mice leads to defects in the peripheral and central nervous system and perinatal death. Issue 1 (December 2017) - Hirst, Caroline; Stamp, Lincon; Bergner, Annette; Hao, Marlene; Tran, Mai; Morgan, Jan; Dutschmann, Matthias; Allen, Andrew; Paxinos, George; Furlong, Teri; McKeown, Sonja; Young, Heather
Abstract Goldberg-Shprintzen syndrome is a poorly understood condition characterized by learning difficulties, facial dysmorphism, microcephaly, and Hirschsprung disease. GOSHS is due to recessive mutations inKIAA1279, which encodes kinesin family member 1 binding protein (KIF1BP, also known as KBP). We examined the effects of inactivation ofKif1bp in mice. Mice lacking Kif1bp died shortly after birth, and exhibited smaller brains, olfactory bulbs and anterior commissures, and defects in the vagal and sympathetic innervation of the gut.Kif1bp was found to interact withRet to regulate the development of the vagal innervation of the stomach. Although newbornKif1bp −/− mice had neurons along the entire bowel, the colonization of the gut by neural crest-derived cells was delayed. The data show an essentialin vivo role for KIF1BP in axon extension from some neurons, and the reduced size of the olfactory bulb also suggests additional roles for KIF1BP. Our mouse model provides a valuable resource to understand GOSHS.